2019
DOI: 10.3390/en12061153
|View full text |Cite
|
Sign up to set email alerts
|

Illustrating the Benefits of Openness: A Large-Scale Spatial Economic Dispatch Model Using the Julia Language

Abstract: In this paper we introduce a five-fold approach to open science comprised of open data, open-source software (that is, programming and modeling tools, model code, and numerical solvers), as well as open-access dissemination. The advantages of open energy models are being discussed. A fully open-source bottom-up electricity sector model with high spatial resolution using the Julia programming environment is then being developed, describing source code and a data set for Germany. This large-scale model of the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
0
10
0
1
Order By: Relevance
“…The reactive power compensation equipment is configured at nodes to provide enough reactive power for balance. The proposed multi-stage transmission network planning model considering transmission congestion is a mixed integer linear programming model, which can be effectively solved through the commercial solver CPLEX [51,52] in MATLAB. Table 1.…”
Section: Case Studiesmentioning
confidence: 99%
“…The reactive power compensation equipment is configured at nodes to provide enough reactive power for balance. The proposed multi-stage transmission network planning model considering transmission congestion is a mixed integer linear programming model, which can be effectively solved through the commercial solver CPLEX [51,52] in MATLAB. Table 1.…”
Section: Case Studiesmentioning
confidence: 99%
“…In this case, a campus MG scheduling was on time, and the daily operational costs were reduced by 58% using open-source optimization. In reference [19], a completely open-source-based ED environment was established using the open-source programming language Julia and its corresponding open-source optimization solver ECOS; computational capability was verified over a 1-year period for a massive operation dataset measured from a German transmission network. The results demonstrated that the open-source environment is suitable for hourly ED of a large-scale grid.…”
Section: Ref Optimizationmentioning
confidence: 99%
“…Similarly, linearizing the second-stage objective function (9) gives additional inequality constraints expressed by (19) where r4 and r5 are parameters for objective function linearization and S2,t and S3,t are binary variables for objective function linearization at time t. Finally, nonlinear objective functions (1) and (3) are linearized to a set of equality constraints (9), (10), and inequality constraints (15)- (19), which are in the form of an MIP problem tractable for analytic method-based optimization solvers. Figure 5 presents the coupling of the two-stage ED strategy using a modular program architecture, as discussed in Section 2.…”
Section: Module (4)mentioning
confidence: 99%
“…The Joulia package in Julia provides a modelling framework for electricity systems that optimizes dispatch (Weibezahn & Kendziorski, 2019). The generation, storage, and transmission capacities have to be provided as exogenous parameters.…”
Section: Capacityexpansion Within the Broader Ecosystemmentioning
confidence: 99%